SOME ASPECTS OF THE - MATHEW, B. (Annali di Botanica, 2000)
The Juno group of Iris (Mathew, 1981) have been treated taxonomically as a section (sect. Juno), as a subgenus (subg. Scorpiris) and as a separate genus (Juno). Whatever its status, the group, comprising some 57 species, is a morphologically convincing assemblage, occurring in the Mediterranean region eastwards into western and central Asia. The distribution, habitat and characteristics of the group are described.